The platform governance triangle: conceptualising the informal regulation of online content - Robert Gorwa (Internet Policy Review, 2019)
From the new Facebook 'Oversight Body' for content moderation to the 'Christchurch Call to eliminate terrorism and violent extremism online,' a growing number of voluntary and non-binding informal governance initiatives have recently been proposed as attractive ways to rein in Facebook, Google, and other platform companies hosting user-generated content. Drawing on the literature on transnational corporate governance, this article reviews a number of informal arrangements governing online content on platforms in Europe, mapping them onto Abbott and Snidal's (2009) 'governance triangle' model. I discuss three key dynamics shaping the success of informal governance arrangements: actor competencies, 'legitimation politics,' and inter-actor relationships of power and coercion.
Keywords: 300; Platforms; Platform governance; Co-governance; Regulation